2019
DOI: 10.21272/mmi.2019.4-02
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the innovative Total Quality Management tool in small and medium-sized enterprises

Abstract: he present paper falling into the field of innovative management tools explores using the Total Quality Management (TQM) tool in the SME sector in Slovakia, attempting to identify barriers to the use of this tool in the given segment. TQM can be ranked among the innovative management tools that are under investigation and in our contribution, we want to bring a new overview of the use of this tool. Our research was based on foreign research in which the TQM management tool is at the forefront of use. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…TQM is an integrated management concept based on factors that firms must practice through a reference framework, such as the European foundation for quality management excellence model (Periañez-Cristobal et al , 2020). As an approach, TQM offers tools and strategies, including totally involving employees, ensuring teamwork, establishing feedback mechanisms and communicating extensively, which inherently promote innovative management (Gallo et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TQM is an integrated management concept based on factors that firms must practice through a reference framework, such as the European foundation for quality management excellence model (Periañez-Cristobal et al , 2020). As an approach, TQM offers tools and strategies, including totally involving employees, ensuring teamwork, establishing feedback mechanisms and communicating extensively, which inherently promote innovative management (Gallo et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…GTI integrates environmental knowledge with technology. It combines environmental science and technology to create or enhance its current products or services and control the harmful effects of business operations (Gallo et al , 2019) and help conserve resources, such as energy and raw material, and synchronize the economy and environment (Yao et al , 2019).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…According to Balcerzak et al (2017), Data Envelopment Analysis and the Malmquist Index are suitable instruments for measuring the efficiency of various business entities. Gallo et al (2019) recommended applying the Total Quality Management tool in enterprises in Slovakia in achieving business appreciation for its owners and shareholders. In addition, future research could be oriented towards one financial method and towards analyzing all TAs in the tourism sector for the purpose of evaluating certain economic industry.…”
Section: Discussionmentioning
confidence: 99%
“…According to Grmanova and Strunz (2017), efficiency is a relative indicator that reflects a particular entity's results by comparing them with the results of other similar entities. As Mihalcova et al (2017) reported, Gallo et al (2019), the main factor to company success is monitoring the actual market situation. Therefore, a competitive struggle is won only by businesses adequately dedicated to evaluating efficiency and using the right approaches and measuring tools.…”
mentioning
confidence: 99%